Indoor WIFI localization on embedded systems - Apavatjrut,A. (Springer Verlag, 2015)
© Springer-Verlag Berlin Heidelberg 2015. Localization has recently become increasingly important for ubiquitous computing. Most embedded devices require location-based services for monitoring and tracking purposes. Typically the location services provided by these devices can be achieved using global positioning system (GPS). Although GPS can indicate absolute position based on satellite system, several studies have demonstrated its inaccuracy when deployed indoor due to signal degradation from the obstacles and building structures. In this paper, we have developed a testbed that provided indoor positioning services based on multi-lateration technique. The empirical results have shown that appropriate indoor propagation model can improve the positioning accuracy, several propagation models have been studied and statistical models have been proposed for a site-specific environment.